Psychology as a science and the psychobiological approach in the training of the psychologyst - Pereyra R., Andrés (2014)
Psychology is a biosocial science so students should receive adequate training in psychobiology, neuropsychology and social psychology. This has been established in various study centers with worldwide reputation and the development of psychological science should conceive its object of study as a domain of various factors so a proper understanding of the biological and social bases of behaviour is required. The nature of the undergraduate program according to the Curricular Structure of Psychology of San Marcos is presented to see if it meets the aim of a comprehensive scientific education and an optimal professional training of the future psychologist as well as the responsibility the school should take as a commitment to science, technology and social service.